The risk of post-operative pulmonary complications in lung resection candidates with normal forced expiratory volume in 1 s and diffusing capacity of the lung for carbon monoxide: a prospective multicentre study - Ivan Cundrle; Zdenek Merta; Monika Bratova; Pavel Homolka; Ladislav Mitas; Vladimir Sramek; Michal Svoboda; Zdenek Chovanec; Milos Chobola; Lyle J. Olson; Kristian Brat (ERJ Open Research, 2023)
Introduction According to the guidelines for preoperative assessment of lung resection candidates, patients with normal forced expiratory volume in 1 s (FEV1) and diffusing capacity of the lung for carbon monoxide (DLCO) are at low risk for post-operative pulmonary complications (PPC). However, PPC affect hospital length of stay and related healthcare costs. We aimed to assess risk of PPC for lung resection candidates with normal FEV1 and DLCO (>80% predicted) and identify factors associated with PPC. Methods 398 patients were prospectively studied at two centres between 2017 and 2021. PPC were recorded from the first 30 post-operative days. Subgroups of patients with and without PPC were compared and factors with significant difference were analysed by uni- and multivariate logistic regression. Results 188 subjects had normal FEV1 and DLCO. Of these, 17 patients (9%) developed PPC. Patients with PPC had significantly lower pressure of end-tidal carbon dioxide (PETCO2) at rest (27.7 versus 29.9; p=0.033) and higher ventilatory efficiency (V′E/V′CO2) slope (31.1 versus 28; p=0.016) compared to those without PPC. Multivariate models showed association between resting PETCO2 (OR 0.872; p=0.035) and V′E/V′CO2 slope (OR 1.116; p=0.03) and PPC. In both models, thoracotomy was strongly associated with PPC (OR 6.419; p=0.005 and OR 5.884; p=0.007, respectively). Peak oxygen consumption failed to predict PPC (p=0.917). Conclusions Resting PETCO2 adds incremental information for risk prediction of PPC in patients with normal FEV1 and DLCO. We propose resting PETCO2 be an additional parameter to FEV1 and DLCO for preoperative risk stratification.